2020
DOI: 10.20944/preprints202003.0146.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Who Adopts Agroforestry in a Subsistence Economy?

Abstract: Land degradation is a critical issue globally putting our future generations at risk. The decrease in farm productivity over the years is evidence of land degradation severity in Nepal. Among the many strategies in place, agroforestry, which is an integrated tree-based farming, is widely recommended to address this productivity issue. This paper thoroughly examines what influences the choice of agroforestry adoption by farmers and what discourages the adoption. For this, a total of 288 households were surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This emphasizes primarily on the tree production as the first choice, and secondarily on the inter-crops or livestock production. Dhakal and Rai (2020) found minimum adoption rate in Nepal. There are many challenges for this, but broadly we explained the challenges for the development of agroforestry system in Nepal in the following sub-headings: (i) socio-economic constraints of the farmers, (ii) policy and institutional constraints, and (iii) management complexity of agroforestry system itself.…”
Section: Multipurpose High Value Trees Species For Timber Human Nutrmentioning
confidence: 93%
“…This emphasizes primarily on the tree production as the first choice, and secondarily on the inter-crops or livestock production. Dhakal and Rai (2020) found minimum adoption rate in Nepal. There are many challenges for this, but broadly we explained the challenges for the development of agroforestry system in Nepal in the following sub-headings: (i) socio-economic constraints of the farmers, (ii) policy and institutional constraints, and (iii) management complexity of agroforestry system itself.…”
Section: Multipurpose High Value Trees Species For Timber Human Nutrmentioning
confidence: 93%
“…In a recent study conducted by Dhakal and Rai (2020), the adoption of agroforestry practices showed a positive impact on the provision of extension services. Thus, extension workers provide information to the farmers and help to clarify their doubts (Dhakal and Rai, 2020). On the contrary, even though farmers had frequent contacts with extension workers they may not have received the necessary information and support for agroforestry as most government extension workers are not knowledgeable in agroforestry and hence not able to deliver the technology and practices suitable for farmers (Neupane et al, 2002).…”
Section: Agrobiodiversity Management Activities Donementioning
confidence: 98%
“…However, women dominant ethnic minorities had more constraints in adopting agroforestry compared to men due to the lack of land and labor, lack of knowledge, low educational level, and poor access to extension constrained adoption (Catacutan and Naz, 2015). In a recent study conducted by Dhakal and Rai (2020), the adoption of agroforestry practices showed a positive impact on the provision of extension services. Thus, extension workers provide information to the farmers and help to clarify their doubts (Dhakal and Rai, 2020).…”
Section: Agrobiodiversity Management Activities Donementioning
confidence: 99%
“…However, women dominant ethnic minorities had more constraints in adopting agroforestry compared to men due to the lack of land and labor, lack of knowledge, low educational level, and poor access to extension constrained adoption (Catacutan and Naz, 2015). In a recent study conducted by Dhakal and Rai (2020), the adoption of agroforestry practices showed a positive impact on the provision of extension services. Thus, extension workers provide information to the farmers and help to clarify their doubts (Dhakal and Rai, 2020).…”
Section: Agrobiodiversity Management Activities Donementioning
confidence: 99%